Cambodian Therapists' Perspectives of Western-based Psychotherapy Models: Addressing the Challenges for Service Providers. Issue 1 (2nd April 2020) - Seponski, Desiree M.; Lewis, Denise C.; Bermudez, J. Maria; Sotelo, Joan Marianne
ABSTRACT: Therapy models developed for Western nations are being imported into Cambodia, yet there is limited research on the effectiveness or native experiences of these therapeutic practices. We present a responsive evaluation of Cambodian therapists' perspectives regarding the use of Western-based therapy models. Utilizing responsive evaluation methodology, qualitative data were triangulated across multiple stakeholders ( N = 95) and multiple methods. Results indicated that, regardless of preferred model, using Western-based therapy presents challenges at individual, family, agency, community, and cultural levels. Participants emphasized that for imported therapeutic models to be culturally responsive and have acceptance and impact in Cambodia, the challenges within Cambodia's mental health field must first be considered.